Association of TNF (rs1800629) promoter polymorphism and schistosomiasis with sub‐microscopic asymptomatic Plasmodium falciparum infections in a schistosomiasis‐endemic area in Zimbabwe. Issue 3 (13th December 2020) - Vengesai, Arthur; Marume, Amos; Midzi, Herald; Kasambala, Maritha; Naicker, Thajasvarie; Mduluza, Takafira
Abstract: Objectives: Infection with Plasmodium falciparum parasites may result in a wide spectrum of symptoms ranging from asymptomatic to mild or severe. A number of factors are associated with this heterogeneous response to P .  falciparum infection. In the present study, associations of sub‐microscopic asymptomatic P. falciparum with Schistosoma species and TNF (rs1800629) polymorphism were investigated. Methods: 361 clinically healthy primary school children were microscopically screened for S. haematobium, S. mansoni and P. falciparum . Sub‐microscopic asymptomatic P. falciparum infections were determined by PCR. Genotypic profiles were identified using ARMS‐PCR. Logistic regression was used to assess the association of sub‐microscopic asymptomatic P. falciparum with Schistosoma species and TNF (rs1800629) polymorphism. Results: 17.2% of the children were infected with S. mansoni, and 27.4% were infected with S. haematobium . Microscopic examination of thick smears detected only one child infected with P. falciparum . Based on PCR results, 46.1% were infected with sub‐microscopic asymptomatic P. falciparum . Children carrying heterozygous AG (OR: 16.964, 95% CI: 0.496–586.547) and homozygous GG (OR: 2.280, 95% CI: 0.111–46.796) genotypes of rs1800629 were associated with an increased likelihood of sub‐microscopic asymptomatic P. falciparum infections compared with those carrying homozygous AA genotype. Children without S. haematobium infections (OR: 1.051, 95% CI: 0.146–8.985) and S. mansoni (OR: 2.658, 95% CI: 0.498–14.184) also had an increased likelihood (risk) of being infected with sub‐microscopic asymptomatic P. falciparum compared with the Schistosoma‐ infected groups. However, all the associations observed were not statistical significant. Conclusion: No associations were observed between rs1800629 and schistosomiasis with sub‐microscopic asymptomatic P. falciparum infections. This study also reports a high prevalence of sub‐microscopic asymptomatic P. falciparum infection concomitant with low malaria transmission. Abstract : Objectifs: L'infection par les parasites P. falciparum peut entraîner un large éventail de présentations allant d'asymptomatiques à bénignes ou sévères. Un certain nombre de facteurs sont associés à cette réaction hétérogène à l'infection à P. falciparum . Dans la présente étude, les associations entre la présentation asymptomatique sous‐microscopique de P. falciparum avec les espèces de Schistosoma et le polymorphisme du TNF (rs1800629) ont été investiguées. Méthodes: 364 écoliers du primaire en bonne santé clinique ont subi microscopique pour S. haematobium, S. mansoni et P. falciparum . Les infections asymptomatiques sous‐microscopiques à P. falciparum ont été déterminées par PCR. Les profils génotypiques ont été identifiés en utilisant ARMS‐PCR. La régression logistique a été utilisée pour évaluer l'association entre la présentation asymptomatique sous‐microscopique de P. falciparum avec les espèces de Schistosoma et le polymorphisme du TNF (rs1800629). Résultats: Parmi les enfants, 17, 2% étaient infectés par S. mansoni et 27, 4% étaient infectés par S. haematobium . L'examen microscopique de frottis épais n'a détecté qu'un seul enfant infecté par P. falciparum . D'après les résultats de la PCR, 46, 1% étaient infectés par P. falciparum asymptomatique sous‐microscopique. Les enfants porteurs des génotypes hétérozygotes AG (OR: 16, 964 ; IC95%: 0, 496‐586, 547) et homozygotes GG (OR: 2, 280 ; IC95%: 0, 111‐46, 796) de rs1800629 étaient associés à une probabilité accrue d'infections asymptomatiques sous‐microscopiques à P. falciparum par rapport à ceux porteurs du génotype homozygote AA. Les enfants sans infection à S. haematobium (OR: 1, 051 ; IC95%: 0, 146‐8, 985) et S. mansoni (OR: 2, 658 ; IC95%: 0, 498 à 14, 184) présentaient également une probabilité (risque) accrue d'être infectés par P. falciparum asymptomatique sous‐microscopique par rapport à ceux infectés par Schistosoma . Cependant, toutes les associations observées n'étaient pas statistiquement significatives. Conclusion: Aucune association n'a été observée entre le rs1800629 et la schistosomiase avec des infections asymptomatiques sous‐microscopiques à P. falciparum . Cette étude rapporte une prévalence élevée d' infection asymptomatique sous‐microscopique à P. falciparum concomitante à une faible transmission du paludisme.